Evaluasi Keselamatan dan Kesehatan Kerja (K3) di Ruang PTM UPTD Puskesmas Baktiya Barat Kec. Baktiya Barat, Kab. Aceh Utara - Mansura Feby Amanda; Tina Maharani (Pusat riset dan Inovasi Nasional, 2025)
Occupational Health and Safety (K3) is an effort to provide safety guarantees and improve the health status of workers/laborers by preventing work-related accidents and diseases, controlling workplace hazards, health promotion, treatment and rehabilitation. Occupational Health and Safety efforts include workforce, work methods/methods, work tools, work processes and work environment. In the PTM room at the West Baktiya Health Center, the space is quite narrow due to the large number of patients visiting, so there is untidiness in the room even though the AC and windows are used. However, having 2 tables in the room makes the room increasingly narrow and difficult to work comfortably. This research aims to find out an overview of the implementation of Occupational Safety and Health in the PTM room. This research is a qualitative descriptive research with a case study design. The subjects of this research were 3 officers in the PTM room. The object of this research is the implementation of K3 and PTM rooms at the West Baktiya Community Health Center. Data was collected by participant observation and semi-structured interviews with informants. The risk factors for the PTM room at the West Baktiya Health Center, seen from occupational safety and health factors, are that it is quite clean, no animals were found that cause disease transmission such as cockroaches, rats and others. There are no occupational safety and health signs and standard operational procedures related to occupational safety and health, while fire prevention in the PTM room at the West Baktiya Public Health Center and the West Baktiya Community Health Center itself is quite good with APAR. There needs to be signs regarding occupational safety and health and SOPs regarding occupational safety and health, especially in the PTM room.